Welding repairing of cracks in cast iron covers - Félix Ramos Morales; Eduardo Manuel Díaz Cedré; Juan Alberto Pozo Morejón; Enrique Velásquez Pérez; Alexis Aurelio Maza Sánchez; Ómar García Manresa; Alejandro Duffus Scott (Revista Facultad de Ingeniería Universidad de Antioquia, 2005)
The welding repair technology of a cast iron cover of a drying cylinder from a paper mill is presented. The results of the base metal characterization are shown; possible reasons that originated the appearance of cracks in previous reparation are discussed; the undertaken decisions are explained in order to guide the process of a cover repair.